Dynamic Response of Commuter Rail Vehicle under Lateral Track Irregularity - HARUN, Mohd Hanif; WAN ABDULLAH, Wan Mohd Zailimi; JAMALUDDIN, Hishamuddin; ABD RAHMAN, Roslan; Khisbullah , Hudha (Trans Tech Publications, Switzerland, 2014)
Lateral track irregularities normally occur when both rail lines have some displacement laterally with respect to the original track due to prolonged exposure to sun’s heat, or may also arise from specific features such as switch and crossing work of track. These track irregularities will cause unwanted body vibration of commuter rail vehicle. These vibrations have to be suppressed for the purpose of ride comfort. This paper presents two control strategies in semi-active suspension systems which are PID and disturbance rejection control to improve passenger ride comfort. A half car model of commuter rail vehicle with three-degree-of-freedom (3-DOF) was developed based on Newton's Second Law. Vibration analyses based on simulation results in time domains are compared with passive system using MATLAB-Simulink software. The results show that the semi-active controllers are able to suppress rail vehicle body responses effectively.